Teknik Pengolahan Citra Digital Berdomain Spasial untuk Peningkatan Citra Sinar-X - Priyawati, Diah (Universitas Muhammadiyah Surakarta, 2011)
In line with the growing use of computers in medicine, the perceived needs of the image data in digital format. The digital format allows for storage of image data in the computer and processes for further image analysis. Available images today are analog images, the necessary process of digitization with digitizer equipment.The image obtained is not necessarily as expected. Supporting equipment, film, and the scanner has a part in creating the image.Quality of image enhancement is needed to create a quality image allows physicians in diagnosing and minimize the possibility of error analysis.?One of the digital image processing techniques is improving the quality of the image (image enhancement). This is done to obtain a good image after a loss of quality during the process of digitizing the image. Image enhancement techniques are divided into two parts. They are spatial domain and frequency domain. This study uses the spatial domain technique which consists of two stages, such as point operation and mask operation. Image experiments performed with several samples such as thorak, collar bone, bone, body tissue, and the image of the hand. Some sample images have different characteristics but the process of image enhancement have in common that will be improving the image brightness.?Combining the methods of image enhancement performed to get the final digital image that has good qualities, such as histogram function,sharpen function, and continued with the function of a negative image. The final result of the digital image after processing showed that the better image quality.?